STUDY OF THE EFFECT OF CYANO SUBGROUP ON THE ELECTRONIC PROPERTIES OF AZULENE MOLECULE:B3LYP-DFT CALCULATION - Jaber, Ghaidaa. A. Hafedh; Ghalib, Basim Abdullattif; Abbood, H. I. (European Scientific Journal, ESJ, 2014)
Theoretical study of the effect of cyano subgroup on the electronic properties of azulene molecule was performed using DFT with B3LYP/6-31(d,p)basis set. The optimized structure, total energies, electronic states, energy gaps, ionization potentials, electron affinities, chemical potentials, global hardness, softness, global electrophilictity, dipole moment and dipole polarizability were calculated. The harmonic vibrational frequencies calculated and compared with available experimental data. The results showed a decrease in energy gap and improve the electronic properties for the new structures.